Stylistic Characteristics Of Some Lexical Units Used In Uzbek Dramas (Zien Journal of Social Sciences and Humanities, 2022)
This article discusses some of the considerations for the lexical analysis of Uzbek dramatic works and the role of lexemes of a limited layer in enhancing the artistic effectiveness of these works